Rancang Bangun Angklung Elektrik dengan Mode Otomatis dan Manual Menggunakan Teknologi Mikrokontroler dan Smartphone - Nur Hanafi, Ilham; Supriyono, Supriyono; Susanti , Hera (P3M Politeknik Negeri Cilacap, 2025)
Angklung is a traditional Indonesian musical instrument originating from West Java. Angklung is composed of two to four bamboo tubes tied with rattan ropes and played by shaking them. The existence of angklung is currently starting to be replaced by modern musical instruments. This research aims to produce angklung integrated with microcontroller and smartphone technology. The use of microcontroller technology allows angklung to be automated without changing the character of the original art. This research method uses a quantitative approach from the design stage to the final test. The research showed that angklung successfully played songs automatically and manually. The tone suitability test results reach 100%. The sound intensity test recorded an average of 86.9 dB in automatic mode and 88.2 dB in manual mode. The power consumption test shows power usage of 1,378 Watts in automatic mode and 1,461 Watts in manual mode.